An Analytical Study on Contemporary Requisites for Niṣab of Zakat in the Light of Opinions of Fuqhā-e-Arba’a - Khan, Javed; Ahmed, Muhammad Mushtaq; Atta Ullah (Journal of Islamic and Religious Studies, 2020)
Zakat is one of the main pillars of Islam. On one hand, it purifies the income of the wealthy people, on the other hand, it helps the needy people hence the social value of Islam and brotherhood is promoted. The niṣāb of few things are very clear as mentioned in aḥādīth in quit unambiguous manner just like nisāb of gold, silver, and livestock, etc. However in a situation when a person’s wealth is a mixture of a different kind of Amwāl-e-zakat and none of them reach to the limit of nisāb, especially in the case of gold, silver, and modern-day paper currency, in this case, whether gold, silver or paper shall be combined for the obligation of zakat or not? Imam Malik, Imam Abū Yūsuf and Imam Muhammad are of the view that the merger shall be based on its quantity/parts((ضم بالاجزاء. On the other hand, according to Imam Abū Ḥanifa, the merger shall be based on the price of gold and silver and the person should be considered nisāb holder if the price of the combined assets reaches the price of nisāb of silver. The above principle shall also be applied for Uzḥiyyah as well. Currently, due to the huge difference in the price of silver and gold, if we take the merger of different assets based on price, people who are not even secure from financial worries become nisāb holder and they have to pay zakat as well as Uzḥiyyah. In this paper, Zakat and its conditions are briefly defined, the issue of the combination of various niṣābs is elaborated, and the modern-day problems in light of the impact of the price of silver on the combination of niṣābs are discussed along with the recommendations.